Modern Technology Advances with Benefits for Humanity to Demonstrate Design with Conventional Sources Islamic - Nuke Puji Lestari Santoso; Amitkumar Dudhat; Husni Teja Sukmana; Aditya Mardiansyah; Marviola Hardini (International Journal of Cyber ​​and IT Service Management (IJCITSM), 2021)
There is an urgent interest among Muslims to participate in broader religious thought activities regarding the nature of modern technology in response to the refutation presented by the ideals of current technology. The impact and use on understanding modern technology cannot be limited. It is so much more pervasive because it conditions ideas, creates our goals and desires. In order to measure modern technology from within the framework of Islamic ethics and design the Islamic paradigm, this is very important by looking at psychological, spiritual, social, moral and circles of the latest postmodernist technology. For holistic insight and moral enhancement of technology, fortitude and practical appropriateness to respond to the latest (contemporary) incident produced due to technology that is holy and ethical poor. Maqashid al-syar'ah hold a useful asset. Muslims should review their traditional notions of Advantage (maṣlaḥah) along with take advantage of these fundamental religious ethics. The design of technological development is beneficial for mankind, because modern technology is infused through It is having a plan all by itself regarding good activities. The intense problem of the Islamic background is which kind of human needs (maṣlaḥah) intense a religion legal discussion can deal with the set of technological values. Muslim jurists, when assessing modern technology, often make use of expressions that describe the optimistic predictions of technology when it comes to human success. This resulted in most of them interpreting human benefit (maṣlaḥah) in terms of technology and issuing fatwas. This makes them be given a particularistic technique to the effect of cutting-edge generation with out considering the effect that current era would possibly have on Muslim life. In this article, it is argued that the contextual-important philosophy of contemporary-day era describes one of the preconditions for outlining what constitutes a reputable human interest (maṣlaḥah). This may be accomplished whilst on the identical time increasing the scope of Islamic Goals (maqashid al-syar'ah) to consist of critical lectures. It links the dual hermeneutic action between the Islamic (time) conception of human goodness (maṣlaḥah) and the axiological contextual perception of the problem during the model of technological development.